National Bibliography in Brazil and Sri Lanka in Electronic Age - Alentejo, Eduardo; Ramanan, T. (Qualitative and Quantitative Methods in Libraries, 2019)
It treats about current and general national bibliography in Brazil and Sri Lanka. It compares both national bibliography due to IFLA guidelines to answer: how the Brazil and Sri Lanka National Bibliographies are organized? This qualitative research is based on the International and Comparative Librarianship approach. From IFLA Guidelines, we identified six dimensions to compare similarities and differences between the National Bibliographies. Brazilian National Bibliography is provided through the current National Library's OPAC and Sri Lanka produces monthly its own national publishing. Since the obligation of legal deposit and the task of bibliographic record, both National Bibliographies provide social benefits such as national safeguard.